Use of Pulsed Electric Field as a Low-Temperature and High-Performance “Green” Extraction Technique for the Recovery of High Added Value Compounds from Olive Leaves - Vasileios M. Pappas; Achillia Lakka; Dimitrios Palaiogiannis; Eleni Bozinou; George Ntourtoglou; Georgia Batra; Vassilis Athanasiadis; Dimitris P. Makris; Vassilis G. Dourtoglou; Stavros I. Lalas (Beverages, 2021)
Olive leaves (OLL), an agricultural waste by-product, are considered a significant bioresource of polyphenols, known as bioactive compounds. This study evaluates the pulsed electric field (PEF) technique for the extraction of polyphenols from OLL. The study parameters included a series of “green” solvents (ethanol, water as well as mixtures of them at a 25% step gradient) and different input values for the pulse duration of PEF. The phytochemical extraction degree was evaluated using total phenol concentration (Folin–Ciocalteu method) and high-performance liquid chromatography (HPLC) analyses, while the antioxidant activity was assessed using differential scanning calorimetry (DSC). The results obtained from the PEF extracts were compared with those of the extracts produced without the PEF application. The highest PEF effect was observed for aqueous ethanol, 25% v/v, using a pulse duration of 10 μs. The increase in the total polyphenols reached 31.85%, while the increase in the specific metabolites reached 265.67%. The recovery in polyphenols was found to depend on the solvent, the pulse duration of treatment and the structure of the metabolites extracted.